Prawno-finansowe aspekty wykorzystania w Polsce odnawialnych źródeł energii w kontekście realizacji konstytucyjnej zasady zrównoważonego rozwoju - Maciej Rudnicki (Studia Ecologiae et Bioethicae)
The article describes the use renewable sources of energy particularly with regard to National Energy Policy in order to achieve good ecological results, principally through the reduction of the use of Greenhouse gases.